The Effect of Environmental, Social, Governance Disclosure and Intellectual Capital on Profitability - Ni Made Widiani; Eka Ardhani Sisdyani (E-Jurnal Akuntansi, 2025)
Increased stakeholder demands for information transparency and social responsibility have prompted companies to disclose information related to environmental, social, and governance issues and to consider intellectual capital as a strategic asset in increasing profits. The objective of this study is to analyze the impact of Environmental, Social, and Governance (ESG) disclosure and intellectual capital on the profitability of the energy sector listed on the Indonesia Stock Exchange (IDX) for the period 2017-2023. The sample was selected using a purposive sampling approach and resulting in 146 observations from 42 companies. Data analysis was conducted using panel data regression techniques through STATA-17 software. The research findings indicate that only governance disclosure and intellectual capital have a positive impact on profitability. Keywords: Environmental Disclosure; Social Disclosure; Governance Disclosure; Intellectual Capital; Profitability